Cross-Modal Conflict Increases With Time-on-Task in a Temporal Discrimination Task - Matuz, András; Van der Linden, Dimitri; Topa, Kristóf; Csathó, Árpád (Frontiers in Psychology, 2019)
The modality appropriateness hypothesis argues that the auditory modality is preferred over the visual modality in tasks demanding temporal operations, hence we predicted that responses to visual stimuli would be more sensitive to the detrimental effect of Time-on-Task. We used a bimodal temporal discrimination task. The factors were durational congruency between the modalities, and the direction of modality-transmission. Participants needed to decide the duration of the cued stimulus (visual or auditory). The first 5 blocks of the task lasted about 1.5 hours without rest (Time-on-Task [ToT] period). The participants then had a 12-minute break followed by an additional block of trials. Subjective fatigue, reaction time, error rates and electrocardiographic data were recorded. In the visual modality we found an enhanced congruency effect as a function of ToT. The cost of attentional shifting was higher in the auditory modality, but remained constant, suggesting that processing of auditory stimuli is robust against the effects of fatigue. Performance did not improve after the break, indicating that the effects of fatigue could not be overcome by taking a brief break. The heart rate variability (HRV) data showed that vagal inhibition increased with ToT, but this increase was not associated with the changes in performance.